2019
DOI: 10.1155/2019/6364390
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Serum hsCRP and Urinary Alpha1-Microglobulin in Patients with Type 2 Diabetes Mellitus

Abstract: This study aimed to investigate the association of serum hsCRP and urinary A1MG in patients with T2DM. Numerous investigations have proven that serum hypersensitive C-reactive protein (hsCRP) concentration in patients with type 2 diabetes mellitus (T2DM) is increased. Also, increased urinary alpha-1 microglobulin (A1MG) can be an early sign of renal damage, primarily on the proximal tubules in T2DM. Little information is available with respect to the associations of serum hsCRP levels and urinary A1MG in T2DM.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…Of the laboratory parameters with less than the required 400 baseline values, it is of interest that brain natriuretic peptide, C-reactive protein and urinary alpha-1 microglobulin were greater than the ULN in more than 10% of the subjects as according to literature these three laboratory biomarkers have been shown to be elevated in individuals with diabetes. 12,13 This data, although with less than 400 subjects, may, therefore, be useful in better understanding the more currently esoteric laboratory parameters. The 28% of laboratory parameters being potentially different from the HVRR further support the pilot study and general medical judgement that it is not uncommon for laboratory parameter values to be different from the HVRR in patient populations.…”
Section: Discussionmentioning
confidence: 99%
“…Of the laboratory parameters with less than the required 400 baseline values, it is of interest that brain natriuretic peptide, C-reactive protein and urinary alpha-1 microglobulin were greater than the ULN in more than 10% of the subjects as according to literature these three laboratory biomarkers have been shown to be elevated in individuals with diabetes. 12,13 This data, although with less than 400 subjects, may, therefore, be useful in better understanding the more currently esoteric laboratory parameters. The 28% of laboratory parameters being potentially different from the HVRR further support the pilot study and general medical judgement that it is not uncommon for laboratory parameter values to be different from the HVRR in patient populations.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, UA1MG freely passes through the glomerular membranes, of which almost 99% is reabsorbed and catabolized by the proximal tubular cells [ 17 ]. Alpha1-microglobulinuria can be induced by glomerular dysfunction and reabsorption dysfunction of renal tubules [ 17 , 18 ]. In other words, UA1MG reflects not only glomerular function but also reflects tubular reabsorbing function.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have indicated that UA1MG also participates in the inflammation process. As mentioned above, elevated UA1MG was related to higher plasma levels of CRP in patients with type 2 diabetes mellitus and myocardial infarction [ 14 , 18 ]. Although previous studies tended to describe A1MG as an antioxidant molecule, an increasing number of studies have questioned its protective role.…”
Section: Discussionmentioning
confidence: 99%
“…A few studies have reported an inverse association between the hs-CRP level and GFR [ 29 , 30 ]. A recent study has also reported a link between hs-CRP elevation and urinary alpha-1 microglobulin (A1MG), an early sign of renal damage, in type II diabetes patients [ 31 ]. Our study provided evidence of the linkage of systemic inflammation and subclinical RI in seemingly healthy middle-aged and elderly community populations.…”
Section: Discussionmentioning
confidence: 99%